2011
DOI: 10.1107/s1600536811014024
|View full text |Cite
|
Sign up to set email alerts
|

(E)-1-(4-Aminophenyl)-3-(naphthalen-2-yl)prop-2-en-1-one

Abstract: The mol­ecule of the title chalcone derivative, C19H15NO, exists in a trans configuration with respect to the C=C double bond. The mol­ecule is slightly twisted with a dihedral angle of 6.12 (12)° between the benzene ring and the naphthalene ring system. The prop-2-en-1-one bridge is nearly planar, with an r.m.s. deviation of 0.0194 (2), and makes dihedral angles of 8.05 (19) and 11.47 (18)° with the benzene ring and the naphthalene ring system, respectively. In the crystal, mol­ecules are linked by N—H⋯O hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…The asymmetric unit of the title compound ( Fig. 1) (Allen et al, 1987) and angles are within normal ranges and are comparable to those found in a related structure (Kobkeatthawin et al, 2011).…”
Section: S1 Commentsupporting
confidence: 78%
See 1 more Smart Citation
“…The asymmetric unit of the title compound ( Fig. 1) (Allen et al, 1987) and angles are within normal ranges and are comparable to those found in a related structure (Kobkeatthawin et al, 2011).…”
Section: S1 Commentsupporting
confidence: 78%
“…For the preparation and applications of chalcones, see: Mori et al (2003); Kumar et al (2006); Amir et al (2008); Atwal et al (1990). For a related structure, see: Kobkeatthawin et al (2011). For reference bond lengths, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%